IMPROVING THE SKILLS OF STORY THROUGH THE APPLICATION OF THE GROUP INVESTIGATION LEARNING MODEL - Hijrah Baharu (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study was to improve storytelling skills through the application of the Group Investigation learning model to VII grade students of Muhammadiyah Limbung Middle School. With a total of 24 students. Data collection techniques used in this study are: (a) students' learning outcomes in English are collected by giving tests at the end of each cycle, (b) data about the teaching and learning process are collected using observation sheets. The data that has been c0ollected is analyzed quantitatively. The results of the analysis showed an increase in quantitative learning outcomes marked by an increase in the average score of students, from 69.16 in the first cycle to 78.12 in the second cycle of an ideal score of 100. Qualitatively, an increase in the quality of the learning process is a change in the attitudes of students marked by: (a) Increasing the frequency of student attendance, (b) The activeness of students in the learning process, (c) The more students pay attention to the teacher's explanation, (d) The more students who ask questions and answer assignments correctly, (e) Increasingly less students who ask for guidance and ask to be explained about a concept.